A Hetero-Multimeric Chitinase-Containing Plasmodium falciparum and Plasmodium gallinaceum Ookinete-Secreted Protein Complex Involved in Mosquito Midgut Invasion - Patra, Kailash P.; Kaur, Hargobinder; Kolli, Surendra Kumar; Wozniak, Jacob M.; Prieto, Judith Helena; Yates, John R.; Gonzalez, David J.; Janse, Chris J.; Vinetz, Joseph M. (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria parasites are transmitted by Anopheles mosquitoes. During its life cycle in the mosquito vector the Plasmodium ookinete escapes the proteolytic milieu of the post-blood meal midgut by traversing the midgut wall. This process requires penetration of the chitin-containing peritrophic matrix lining the midgut epithelium, which depends in part on ookinete-secreted chitinases. Plasmodium falciparum ookinetes have one chitinase (PfCHT1), whereas ookinetes of the avian-infecting parasite, P. gallinaceum, have two, a long and a short form, PgCHT1 and PgCHT2, respectively. Published data indicates that PgCHT2 forms a high molecular weight (HMW) reduction-sensitive complex; and one binding partner is the ookinete-produced von Willebrand A-domain-containing protein, WARP. Size exclusion chromatography data reported here show that P. gallinaceum PgCHT2 and its ortholog, P. falciparum PfCHT1 are covalently-linked components of a HMW chitinase-containing complex (> 1,300 kDa). Mass spectrometry of ookinete-secreted proteins isolated using a new chitin bead pull-down method identified chitinase-associated proteins in P. falciparum and P. gallinaceum ookinete-conditioned culture media. Mass spectrometry of this complex showed the presence of several micronemal proteins including von Willebrand factor A domain-related protein (WARP), ookinete surface enolase, and secreted ookinete adhesive protein (SOAP). To test the hypothesis that ookinete-produced PfCHT1 can form a high molecular homo-multimer or, alternatively, interacts with P. berghei ookinete-produced proteins to produce an HMW hetero-multimer, we created chimeric P. berghei parasites expressing PfCHT1 to replace PbCHT1, enabling the production of large numbers of PfCHT1-expressing ookinetes. We show that chimeric P. berghei ookinetes express monomeric PfCHT1, but a HMW complex containing PfCHT1 is not present. A better understanding of the chitinase-containing HMW complex may enhance development of next-generation vaccines or drugs that target malaria transmission stages.